Music in Quarantine: Connections Between Changes in Lifestyle, Psychological States, and Musical Behaviors During COVID-19 Pandemic - Terasawa, Hiroko; Matsubara, Masaki; Goudarzi, Visda; Sadakata, Makiko (Frontiers in Psychology, 2021)
Music is not only the art of organized sound but also a compound of social interaction among people, built upon social and environmental foundations. Since the beginning of the COVID-19 outbreak, containment measures such as shelter-in-place, lockdown, social distancing, and self-quarantine have severely impacted the foundation of human society, resulting in a drastic change in our everyday experience. In this paper, the relationships between musical behavior, lifestyle, and psychological states during the shelter-in-place period of the COVID-19 pandemic are investigated. An online survey on musical experience, lifestyle changes, stress level, musical behaviors, media usage, and environmental sound perception was conducted. The survey was conducted in early June 2020. Responses from 620 people in 24 countries were collected, with the large proportion of the responses coming from the U.S. (55.5%) and India (21.4%). Structural equation modeling (SEM) analysis revealed causal relationships between lifestyle, stress, and music behaviors. Elements such as stress-level change, work risk, and staying home contribute to changes in musical experiences, such as moderating emotion with music, feeling emotional with music, and being more attentive to music. Stress-level change was correlated with work risk and income change, and people who started living with others due to the outbreak, especially with their children, indicated less change in stress level. People with more stress-level change tended to use music more purposefully for their mental well-being, such as to moderate emotions, to influence mood, and to relax. In addition, people with more stress-level change tend to be more annoyed by neighbors' noise. Housing type was not directly associated with annoyance; however, attention to environmental sounds decreased when the housing type was smaller. Attention to environmental and musical sounds and the emotional responses to them are highly inter-correlated. Multi-group SEM based on musicians showed that the causal relationship structure for professional musicians differs from that of less-experienced musicians. For professional musicians, staying at home was the only component that caused all musical behavior changes; stress did not cause musical behavior changes. Regarding Internet use, listening to music via YouTube and streaming was preferred over TV and radio, especially among less-experienced musicians, while participation in the online music community was preferred by more advanced musicians. This work suggests that social, environmental, and personal factors and limitations influence the changes in our musical behavior, perception of sonic experience, and emotional recognition, and that people actively accommodated the unusual pandemic situations using music and Internet technologies.